2004
DOI: 10.1063/1.1799613
|View full text |Cite
|
Sign up to set email alerts
|

Transcription-driven twin supercoiling of a DNA loop: A Brownian dynamics study

Abstract: The torque generated by RNA polymerase as it tracks along double-stranded DNA can potentially induce long-range structural deformations integral to mechanisms of biological significance in both prokaryotes and eukaryotes. In this paper, we introduce a dynamic computer model for investigating this phenomenon. Duplex DNA is represented as a chain of hydrodynamic beads interacting through potentials of linearly elastic stretching, bending, and twisting, as well as excluded volume. The chain, linear when relaxed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 28 publications
2
32
0
Order By: Relevance
“…DNA buckling (i.e. the transition to non-B form structures) was not observed in these experiments below a value of ϩ0.058 (69). Therefore, we believe that the positively supercoiled substrates used in our DNA relaxation assays ( Ϸ ϩ0.035 to ϩ0.039) should be free of unusual non-B structures.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…DNA buckling (i.e. the transition to non-B form structures) was not observed in these experiments below a value of ϩ0.058 (69). Therefore, we believe that the positively supercoiled substrates used in our DNA relaxation assays ( Ϸ ϩ0.035 to ϩ0.039) should be free of unusual non-B structures.…”
Section: Resultsmentioning
confidence: 90%
“…However, single molecule experiments suggest that DNA ahead of tracking systems can reach a value as high as ϩ0.110 (69). DNA buckling (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…At a critical point, energetically, it is more feasible for the DNA molecule to rotate around its own helix axis to produce a positively supercoiled domain in front of the RNA polymerase and a negatively supercoiled domain behind it. These two transient supercoiled domains may be relaxed by DNA topoisomerases or cancel each other by diffusion Mielke et al, 2004;Nelson, 1999;Tsao et al, 1989;.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Nelson demonstrated that small natural bends in the DNA helix backbone was able to increase a few thousand fold of torsional stress even in a linear unanchored DNA (Nelson, 1999), this torsional force is sufficient to generate a positively supercoiled domain in front of the RNA polymerase and a negatively supercoiled domain behind it (Nelson, 1999). Another case is a Brownian dynamic study conducted by Mielke et al (Mielke et al, 2004). These studies clearly demonstrated that a transcribing RNA polymerase alone is able to drive the formation of positively and negatively domains in a naked plasmid DNA template.…”
mentioning
confidence: 99%
See 1 more Smart Citation